Barbados : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
In this paper, the following statistical data are presented in detail: national accounts at current prices, index of industrial production, selected sugar statistics, tourism statistics, retail labor index, wage indicators, operations of the consolidated public sector, central governments operations and transfers, summary accounts of the consolidated banking system, selected interest rates, total exports and imports, financial system credit to the private sector, liquidity position of commercial banks, services, investment income, current transfers, summary of external debt, direction of trade, and so on.